ANALISIS PERUBAHAN PITA FREKUENSI 1800 DAN 2100 MHZ TERHADAP PERFORMANSI JARINGAN BASE TRANSCEIVER STATION - ., Syarif Muhammad Faisal (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
Abstract - In its application, the mobile system has its limitationsÂ Â  Â and isÂ Â  Â oftenÂ Â  Â experienced disturbancesÂ  (interference) Â like Â limited Â talk channels as the result of the increasing number of cellular communication technology user, which is led to â€žblock callâ€Ÿ. The problem with Radio FrequencyÂ Â  (RF)Â  Â signalÂ Â  receptionÂ  Â isÂ  Â alsoÂ  Â an important factor in wireless communication system. The low quality of signal levels caused the frequent call failure or â€ždrop callâ€Ÿ. Therefore, it is necessary to have sustainable monitoring system and analysis towards the performance of theÂ  network system, especially after the government produce the For a review of Necessary Process Monitoring and analysis of the Sustainable Network system, especially with the regulation of the Ministry of Communication Â and Â Information Â No. Â 19 Â / Â 2013 About Â " Â Mekanisme Â dan Â Tahapan Â Pemindahan Alokasi Pita Frekuensi Radio Pada Penataan Menyuluruh Pita Frekuensi Radio 2100 MHz.â€ The monitoring and performance analysis used Key Performance Indicator (KPI) parameters as a benchmark for the network performance and a descriptionÂ Â  of Â theÂ  Â cellularÂ  Â system Â QualityÂ Â  of Service (QoS). The KPI parameters are Call Setup Success Rate (CSSR), Drop Call Rate (DCR), Handover Success rate (HSR), and Traffic Channel Congestion rate (TCH Congestion rate). The results of the test drive of five BTS before and after frequency refarming in 1800 and 2100 MHz, the percentage of SDCCH blocking was not high enough, as determined by PT. Indosat Ooredoo, which is not more than 2%. There are 5 BTS to be observed:Â  Â BTS Â Nipah Â Kuning,Â Â  BTS Â Perum Â 1 Jeruju, BTS Martadinata, BTS Gertak 1 and BTS Gang Semangka. Â  Keywords Â : Frequency band and Parameter Key Performance Indicator (KPI)